2020
DOI: 10.3390/su12177064
|View full text |Cite
|
Sign up to set email alerts
|

Biophilic Design for Restorative University Learning Environments: A Critical Review of Literature and Design Recommendations

Abstract: The influence of environmental design on people’s wellbeing and productivity has been well studied in some settings such as offices, hospitals, and elementary schools, but salutogenic and biophilic design in urban post-secondary educational environments remains understudied and warrants closer investigation. There are unique challenges faced by these students and implementing health promoting and restorative, environmental design strategies could improve the quality of life and learning outcomes of university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…Some of the hospital environment design features that affect a patient's recovery process related to the physical environment are odour, sound, and light (Aripin S., 2007;Chong & Shanshan, 2020). The patients and healthcare workers had high anxiety around hospital environments when the Covid-19 pandemic happened (Peters & D'Penna, 2020). The author also mentioned an empirical research study related to the indoor spaces that are urgently needed to help boost patients' and workers' mental and physical state conditions.…”
Section: Hospital Planning and Designmentioning
confidence: 99%
“…Some of the hospital environment design features that affect a patient's recovery process related to the physical environment are odour, sound, and light (Aripin S., 2007;Chong & Shanshan, 2020). The patients and healthcare workers had high anxiety around hospital environments when the Covid-19 pandemic happened (Peters & D'Penna, 2020). The author also mentioned an empirical research study related to the indoor spaces that are urgently needed to help boost patients' and workers' mental and physical state conditions.…”
Section: Hospital Planning and Designmentioning
confidence: 99%
“…Students associate waterfront spaces with optimal perceived attention restoration effect, followed by vegetation spaces, courtyard spaces and square spaces ( Lu and Fu, 2019 ). The integration of water elements in university design is scarce ( Peters and D’Penna, 2020 ) but studies have revealed that images of nature depicting water are restorative and images of study areas with a water feature are preferred ( Hami and Abdi, 2019 ). Also, when combined with diversified vegetation and various levels of privacy, water scenes provide positive distraction.…”
Section: Connectedness To Nature In Campus Settingsmentioning
confidence: 99%
“…In other words, employees want their built environment to be attractive and accessible with well-developed infrastructure to work and perform at work. The influence of environmental design on people's wellbeing and productivity has been well studied in occupational settings such as offices, hospitals, university campuses, etcetera (Peters & D'Penna, 2020). However, the built environment at the university impacts the emotional stress, happiness, stimulation, cognitive function, social support, belonging, places to wordy or work, lighting, and ventilation (ibid).…”
Section: The Conducive Work Space and Built Environment For Happiness...mentioning
confidence: 99%